ANALISIS KAUSALITAS PERTUMBUHAN EKONOMI, INFRASTRUKTUR DAN PENERIMAAN PAJAK DI PROVINSI SUMATERA BARAT - Farik Hidayah; Zul Azhar; Dewi Zaini Putri (Jurnal Ecogen, 2018)
The aims of this study are to find out whether there is a causal relationship between the variables of economic growth, infrastructure and tax revenue in West Sumatra. This type of research is associative descriptive research, where the data used is secondary data from 1986 to 2016 obtained from the Central Statistics Agency. Which are analysed using the Vector Auto Reggresion (VAR) method to see the reciprocal relationship between variables used. The results of this study have a one-way relationship between infrastructure and economic growth, and there is also a unidirectional relationship between infrastructure and tax revenue in West Sumatera.Keywords: economic growth, infrastructure and tax revenue